Shared spiritual beliefs between adolescents with cancer and their families. Issue 12 (12th September 2020) - Livingston, Jessica; Cheng, Yao I.; Wang, Jichuan; Tweddle, Matthew; Friebert, Sarah; Baker, Justin N.; Thompkins, Jessica; Lyon, Maureen E.
Abstract: Background: FAmily CEntered (FACE) Advance Care Planning helps family decision makers to understand and honor patients' preferences for future health care, if patients cannot communicate. Spiritual well‐being is a key domain of pediatric oncology care and an integral dimension of pediatric advance care planning. Procedure: As part of four‐site randomized controlled trial of FACE for teens with cancer, the functional assessment of chronic illness therapy‐spiritual well‐being‐ version 4 (FACIT‐Sp‐EX‐4) was completed independently by 126 adolescents with cancer/family dyads. The prevalence‐adjusted and bias‐adjusted kappa (PABAK) measured congruence on FACIT‐Sp‐EX‐4. Results: Adolescents (126) had mean age of 16.9 years, were 57% female and 79% White. Religious/spiritual classifications were: Catholic (n = 18), Protestant (n = 76), Mormon (n = 3), none/atheist (n = 22), other (n = 5), and unknown (n = 2). Agreement at item level between spiritual well‐being of adolescents and families was assessed. Three items had ≥90% agreement and Excellent PABAK: "I have a reason for living, " "I feel loved, " "I feel compassion for others in the difficulties they are facing." Three items had <61% agreement and Poor PABAK: "I feel a sense of harmony within myself, " "My illness has strengthened my faith or spiritual beliefs, " "I feel connected to a higher power (or God)." Dyadic congruence was compared by social‐demographics using median one‐way analysis. Male family members (median = 72%) were less likely to share spiritual beliefs with their adolescent than female family members (median = 83%), P = .0194. Conclusions: Family members may not share spiritual beliefs with adolescents and may be unaware of the importance of spiritual well‐being for adolescents.